Perceived Sleep Quality, Mood States, and Their Relationship with Performance among Brazilian Elite Athletes during a Competitive Period - Brandt R. (2017)
© 2017 National Strength and Conditioning Association.Brandt, R, Bevilacqua, GG, and Andrade, A. Perceived sleep quality, mood states, and their relationship with performance among Brazilian elite athletes during a competitive period. J Strength Cond Res 31(4): 1033-1039, 2017 - We described the perceived sleep quality and mood states of elite athletes during a competitive period, and clarified their relationship to athletes' sport performance. Participants were 576 Brazilian elite athletes (404 men and 172 women) of individual and team sports. Mood states were evaluated using the Brunel Mood Scale, whereas perceived sleep quality was evaluated using a single question ("How would you evaluate the quality of your sleep in the last few days?"). Evaluations of mood state and sleep quality were performed up to 60 minutes before national and international sports competitions began. Descriptive and inferential statistics (including logistic regression) were used to evaluate the relationship of sleep quality and mood states with performance (i.e., winning or losing). Athletes typically had good sleep quality and mood states similar to the Iceberg profile (i.e., high vigor and low tension, depression, anger, fatigue, and mental confusion). The Wald test revealed that sleep, anger, tension, and vigor predicted athletes' performance. Specifically, poor sleep quality and low vigor and anger decreased the odds of winning, whereas higher tension increased these odds. The Hosmer-Lemeshow test indicated that the results were sufficiently generalizable. Overall, we observed a significant relationship between sleep and mood states, which in turn both significantly influenced athletes' sports performance. Thus, coaching staff and athletes should monitor athletes' sleep quality before competitions to ensure athletes are in the optimal condition for performance.